TAXATION OF FARMERS BY THE INCOME TAX IN SERBIA - Milošević, Goran; Vuković, Marija; Jovanović, Duško (Economics of Agriculture, 2018)
The tax system must be in accordance with the requirements and interests of the tax authorities, but also with the goals of taxpayers. Fiscal intervention should reflect the taxpayers fscal power as well as certain forms of taxation. In that regard, agricultural production activities are also the subject of taxation as they are conducted by a large number of entities who have different financial positions and conditions of production. The holders of agricultural production activities achieve their goals, and thus the economic interests of the country are fulflled. The government show through various measurements that agriculture is an important economic sector and encourage its growth and development. As an instrument of their economic policy, the government can also use the taxation system for agriculture. Taxation of agriculture leads to the achievement of the economic and fscal goals of the country as well as non-taxation goals. Tax policy measures can, therefore, either encourage or discourage agricultural production activities.